FRI0397 Adherence to EULAR recommendations for the treatment of GOUT. (23rd January 2014) - Khanna, P.; Hagerty, D.; Mischler, R.; Morlock, R.
Abstract : Background: Gout is a relatively common condition with low adherence to urate-lowering therapy (ULT) which leads to frequent flares and disability. To improve patient care the European League Against Rheumatism (EULAR) developed evidence-based recommendations for treatment of gout. Objectives: Assess adherence to the EULAR treatment guidelines in a cohort of gout patients treated with xanthine oxidase inhibitors (XOI) from 5 European nations including France, Germany, Italy, Spain and the United Kingdom (UK). Methods: Data from a quantitative survey of physicians were assessed and results confirmed through in-depth chart audits. Type and initial dose of XOI, presence of kidney disease, use of prophylaxis for flare prevention, serum uric acid (sUA), physician subspecialty and patient factors were evaluated. Data on number of patients initiating ULT, flare prophylaxis (NSAIDs/colchicine/corticosteroids/Cox2s), pattern of titration of allopurinol, and achievement of target sUA≤6mg/dLwithin 12 months of treatment initiation were also collected. Results are presented as proportions or means and standard deviations (SD). Results: 126 rheumatologists and 126 primary care physicians were interviewed. Of 1260 patients, 965 (77%) were treated with either allopurinol or febuxostat. Patient characteristics, treatment and percent achieving sUA≤6 mg/dL are presented in Table 1. Across all countries, majority (85%) of patients were treated with allopurinol. Use of prophylaxis for flares varied significantly by country, with the lowest use in Germany (29%) and highest in Spain (65%, p<0.01). There were significant differences in starting doses of allopurinol (Table 1) and titration above 300mg. Less than 6.5% in France, Germany and Spain were titrated above 300mg whereas 10% in Italy and 34% in the UK achieved a daily dose above 300mg (p<0.01). Over 12 months, number of patients achieving SUA≤6.0 mg/dL differed across the 5 countries (Spain < Germany < France < Italy < UK, Table 1). There was no statistical difference between XO inhibitors in the proportion of patients reaching sUA target (p=0.37). Conclusions: This quantitative survey revealed major differences in practice patterns for initiation of ULT with XOI among 5 major European nations. A large proportion of patients from countries less likely to aggressively titrate XOI did not achieve the EULAR recommended target sUA≤6.0 mg/dL. Even countries that used higher doses of allopurinol had 30% non-response to ULT. This could be reflective of differences among nations in comorbidities of patients, inadequate dosing of ULT and adherence to medications. Significant opportunities exist across all countries to improve management of patients with gout. Disclosure of Interest: P. Khanna Consultant for: Ardea Biosciences, Speakers Bureau: Takeda, Novartis, D. Hagerty Employee of: Ardea Biosciences, R. Mischler Employee of: Ardea Biosciences, R. Morlock Consultant for: Ardea Biosciences